Peningkatan umur simpan kolang-kaling dengan larutan ekstrak kayu manis (Cinnamomum burmannii) dan ekstrak cengkeh (Syzygium aromaticum) sebagai bahan pengawet alami - Otik Nawansih; Haidar Bani Abdillah; Novita Herdiana; Diki Danar Tri Winanti (AGROINTEK, 2022)
Kolang-kaling is a half-ripe palm fruit. Its vitamins and minerals were efficacious in maintaining health. Kolang-kaling damage was characterized by a change in color to brown and a change in texture. Ingredients to maintain the quality for example cinnamon and clove extract. The purpose of this study was to determine the best concentration of cinnamon extract (0.3 %, 0.4 %, 0.5 %) and clove extract (0.4 %, 0.6 %, 0.8 %) as natural preservatives to the shelf life of kolang-kaling with optimal sensory properties. Kolang-kaling in syrup was stored at room temperature and observed the shelf life using conventional methods on days 0, 7, 14, 21, 28 and 35. Observed parameters include shelf life, pH, moisture content, protein, fat, degree of syrup brix, fierce levels, total plate numbers, and hedonic tests. Data analysis uses descriptive methods. The results showed that kolang-kaling in syrup with a concentration of 0.5 % cinnamon and 0.4 % cloves was preferred by hedonic panelists with a score of 3.05. The results of the total plate number test show the results of 3.1 x 104 colonies/gr, which means that it has not been able to meet the provisions of the Total Plate Number of SNI 01-4472-1998.